Genetic engineering, a hope for sustainable biofuel production: review - Paudel, Sudip; Menze, Michael A (International Journal of Environment, 2014)
The use of recently developed genetic engineering tools in combination with organisms that have the potential to produce precursors for the production of biodiesel, promises a sustainable and environment friendly energy source. Enhanced lipid production in wild type and/or genetically engineered organisms can offer sufficient raw material for industrial transesterification of plant-based triglycerides. Bio-diesel, produced with the help of genetically modified organisms, might be one of the best alternatives to fossil fuels and to mitigate various environmental hazards. DOI: http://dx.doi.org/10.3126/ije.v3i2.10644 International Journal of the Environment Vol.3(2) 2014: 311-323